Long-term prognosis associated with early repolarisation pattern in Chinese population with atherosclerotic risk factors. Issue 12 (30th December 2016) - Cheng, Yun-Jiu; Mei, Wei-Yi; Chen, Xu-Miao; Liu, Li-Juan; Zheng, Dong-Dan; Ji, Cheng-cheng; Tang, Kai; Wu, Su-Hua
Abstract : Background: Recent evidence has linked early repolarisation pattern (ERP) to sudden cardiac death (SCD) in patients without structural heart disease. However, no studies have clarified the prognostic value of ERP in people at high risk for atherosclerotic heart disease. Methods: We prospectively assessed the prognostic significance of ERP on ECGs in a community-based population of 18 231 subjects with atherosclerotic risk factors (49.3% men, mean age 64.0 years). Mean follow-up was 7.6 years. Cox models were used to estimate the hazard ratios (HRs) adjusted for possible confounding factors. Results: Compared with those without ERP, subjects with ERP had a significantly increased risk of developing SCD (HR 1.91, 95% CI 1.30 to 2.82), death from coronary heart disease (CHD) (HR 1.80, 95% CI 1.45 to 2.22) and death from any cause (HR 1.35, 95% CI 1.22 to 1.50). ERP was not associated with an increased risk of non-sudden CHD death and non-CHD death. ERP with J wave pattern in inferior leads, high amplitude of J wave pattern, notching configuration and horizontal or descending ST segment indicated a higher risk for SCD. ERP was associated with an absolute risk increase of 52.3 additional SCDs per 100 000 person-years in the population at high risk for atherosclerotic heart disease. Conclusions: ERP is associated with a significantly increased risk for SCD, CHD death and death from any cause in people with atherosclerotic risk factors. The observed association between ERP and all-cause mortality appears to be driven by an association with CHD death, in particular SCD.